Modelo de desarrollo de comercio electrónico b2c en los países menos desarrollados: el caso peruano - Díaz, Antonio (2003)
This research proposes a development model for e-commerce from business to consumer (B2C) in the least developed countries, based on electronic commerce in Peru. To find common characteristics that make it possible to define the model, semi-structured interviews are conducted with three sectors of professionals linked to the development of electronic commerce in Peru: those responsible for the definition of policies and standards on electronic commerce, Internet service providers (ISP), and the managers and directors of companies immersed in electronic commerce activities. It is proposed a priori that the model contemplates the situation of the national technological infrastructure, the diffusion of the means of payment, the situation of the physical distribution and the online purchase culture in Peru.